Improving port hinterland connection capacity: a comparative study of Polish and Belgian cases - Raimonds Aronietis; Jedrzej Gadzinski; Anna Golêdzinowska; Tom Pauwels; Thierry Vanelslander; Rafal Wasil (European Regional Science Association (ERSA), 2011)
The study takes a comparative approach by investigating the situation in the hinterlands of two different port areas in Europe: Antwerp (Belgium) and Gdansk-Sopot-Gdynia agglomeration (Poland). Both port centres have an important road hinterland connection that faces competition from other alternative modes of freight transport. However, the Port of Antwerp is already one of the leading ports of the continent while the ports of Gdansk and Gdynia are at the stage of building their competitive position. Also the importance of inland waterways in the transport systems in these countries is different - Belgium has a functioning network of waterways while Poland still has to develop it. The Belgian case is the E313 motorway, which makes the connection between Antwerp and Liège and further on also Germany. The motorway has competition from both rail and inland waterways, especially in dealing with port-bound traffic. The Albert Canal, which runs mainly in parallel with the motorway, is currently being subject to capacity expansion through the extension and elevation of a number bridges that cross the canal. Rail could specifically benefit from the potential re-activation of the Iron Rhine - an almost parallel connection to the motorway E313 between Antwerp and the German Ruhr area. The Polish case is focused on possible scenarios of freight traffic between Baltic port centre of Gdansk and Gdynia with important international harbour and fast developing regional centre - Bydgoszcz-Torun. At present the main connections between those urban areas are the state road 1, section of motorway A1 and railway CE-65. Gdansk, Torun and Bydgoszcz are also linked with Vistula river (part of international inland waterways E-40 and E-70) but so far it is not used extensively. The cases are analyzed separately. The added value of the paper is the comparative analysis which allows making conclusions that are valid for both environments. The results are of high relevance to policy makers in charge of alleviating port hinterland problems, and also to ports in the current highly competitive environment.
Keywords: 330